PENGEMBANGAN BUKU IMPLEMENTASI PEMBELAJARAN BERBASIS WEB DAN APLIKASI ANDROID UNTUK MEMBAWA KAPABILITAS GURU - Reza Kusuma Setyansah; Andria (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This study aims to determine the results of the process of developing a web-based e-learning implementation book and an android application, as a way to hone the teaching skills of prospective teachers. The instruments in this study were observation sheets, books, and questionnaires. Based on the achievement of the product, product evaluation is needed including validation of material experts and media experts. The stages in this study with the ADDIE model are (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of this study obtained that the web-based e-learning implementation book and android application have fulfilled (1) Validation data with the average results obtained from the media validation sheet from media experts 93.67% and 85 material experts, 33%. (2) seen a positive influence from the results of the post-test with a percentage of 91.68% and (3) shows the response of prospective teachers after using e-learning books in the main field test showed a percentage of 82.68% so that they can hone their ability to teach independently.